2020
DOI: 10.1128/iai.00510-20
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin Exerts an Antibiofilm Effect against Salmonella enterica Serovar Typhimurium rdar Biofilm Formation and Transforms the Physiology towards an Apparent Oxygen-Depleted Energy and Carbon Metabolism

Abstract: Upon biofilm formation, production of extracellular matrix components and alteration in physiology and metabolism allows bacteria to build up multicellular communities which can facilitate nutrient acquisition during unfavorable conditions and provide protection towards various forms of environmental stresses to individual cells. Thus, bacterial cells become tolerant against antimicrobials and the immune system within biofilms. In the current study, we evaluated the antibiofilm activity of the macrolides clari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
(46 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, our findings revealed a reduction in oxidative phosphorylation in clarithromycin‐resistant conditions. In line with our results, a study conducted on Salmonella enterica serovar Typhimurium also demonstrated that exposure to clarithromycin shifted the cellular status toward oxygen and energy depletion, leading to the downregulation of oxidative phosphorylation pathways 68 . This consistent observation underscores the impact of clarithromycin on metabolic processes across different bacterial species, highlighting its potential to induce a common response in cellular energy dynamics.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our findings revealed a reduction in oxidative phosphorylation in clarithromycin‐resistant conditions. In line with our results, a study conducted on Salmonella enterica serovar Typhimurium also demonstrated that exposure to clarithromycin shifted the cellular status toward oxygen and energy depletion, leading to the downregulation of oxidative phosphorylation pathways 68 . This consistent observation underscores the impact of clarithromycin on metabolic processes across different bacterial species, highlighting its potential to induce a common response in cellular energy dynamics.…”
Section: Discussionsupporting
confidence: 90%
“…RNA was isolated from cultures grown on LB 0 plates at 28 °C for 24 h, as described previously [ 30 ]. qPCR assays were performed as described [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…While macrolides selectively affect the translation of messenger RNA into proteins by interacting with the 23S RNA of ribosomes, and prevent 50S ribosomal subunit assembly [ 126 ], transcriptional profiling of the response against subinhibitory concentrations of the semi-synthetic macrolide clarithromycin to prevent ancient rdar biofilm formation of Salmonella typhimurium , a biofilm directed by the transcriptional regulator CsgD via the expression of amyloid curli fimbriae and the exopolysaccharide cellulose, indicated selective upregulation of ribosomal subunit genes with their gene products potentially interacting with clarithromycin. Upregulation of the heat shock stress response with folding and holding chaperons is also indicative of impaired protein homeostasis [ 127 ]. Transcriptional analysis further indicated the redirection of microbial metabolism towards an oxygen- and energy-depleted status where energy is derived from L-arginine catabolism and propane-1,2-diol and ethanolamine degradation rather than by oxidative phosphorylation.…”
Section: Innovative Strategies To Overcome Antimicrobial Tolerance In...mentioning
confidence: 99%